Extraction and rections of caffeine - Mohd. Syafique Nahar Baharuddin. 1987-; Khatijah Zakariah, supervisor; Fakulti Sains (2008)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2008